Penggunaan Sosial Media Sebagai Wadah Promosi TBM Pelita Karangwidoro - Moh Safi'i; Lia Yunaidah; Maryam Ignatia Latifha; Muhammad Refyan Taufikur Shafa; Shifa Amaliah Batara (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Karangwidoro Community Reading Park is a non-profit institution located in Ndoro Hamlet, Malang Regency, East Java. This Community Reading Park has management, which is an obstacle to promoting it to the general public through social media, a less effective means of communication. Therefore, we will develop an effective promotional strategy for Community Reading Parks through social media by creating interesting and informative content such as promotional videos, creating interesting content, and posts related to Community Reading Park activities.